Nanofios crescidos por magnetron sputtering com feixe de vapor em incidência rasante: mecanismo de crescimento das nanoestruturas e características magnéticas. - Verbeno, Carlos Henrique Santos (2019)
In this thesis, an experimental setup was developed for production of W, Co and W/Co nanowires (NWs) on sapphire vicinal surfaces, using sputtering equipment with magnetrons positioned in a confocal geometry, in which the vapor beam reaches the substrate